2016
DOI: 10.4254/wjh.v8.i31.1295
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol use disorder and its impact on chronic hepatitis C virus and human immunodeficiency virus infections

Abstract: Alcohol use disorder (AUD) and hepatitis C virus (HCV) infection frequently co-occur. AUD is associated with greater exposure to HCV infection, increased HCV infection persistence, and more extensive liver damage due to interactions between AUD and HCV on immune responses, cytotoxicity, and oxidative stress. Although AUD and HCV infection are associated with increased morbidity and mortality, HCV antiviral therapy is less commonly prescribed in individuals with both conditions. AUD is also common in human immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 177 publications
(193 reference statements)
0
32
0
Order By: Relevance
“…This is particularly important because of the interaction of heavy alcohol consumption and HCV in causing liver disease (Fuster and Samet, ; Fuster et al., ). Heavy alcohol consumption can potentiate HCV‐related cytotoxicity and oxidative stress (Fuster et al., ), increase the rate of HCV‐induced fibrosis (Fuster and Samet, ) and the risk of liver cirrhosis and hepatocellular carcinoma (Fuster et al., ), and reduce the effect of HCV treatment (Fuster and Samet, ). Individuals with an HCV diagnosis were significantly less likely to be categorized into the lower risk and potentially hazardous/harmful trajectories versus the infrequent drinking trajectory compared to those without HCV.…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly important because of the interaction of heavy alcohol consumption and HCV in causing liver disease (Fuster and Samet, ; Fuster et al., ). Heavy alcohol consumption can potentiate HCV‐related cytotoxicity and oxidative stress (Fuster et al., ), increase the rate of HCV‐induced fibrosis (Fuster and Samet, ) and the risk of liver cirrhosis and hepatocellular carcinoma (Fuster et al., ), and reduce the effect of HCV treatment (Fuster and Samet, ). Individuals with an HCV diagnosis were significantly less likely to be categorized into the lower risk and potentially hazardous/harmful trajectories versus the infrequent drinking trajectory compared to those without HCV.…”
Section: Discussionmentioning
confidence: 99%
“…Subjects with hepatitis C virus infection report a significant alcohol intake [68], and are more prone to alcohol abuse than the general population [69], and alcohol is expected to impact on progression of chronic hepatitis [70]. Hezode et al initially reported a progressive increase in histologic severity and fibrosis in relation to the amount of alcohol intake in chronic HCV infection [59,70]. However, in a similar cohort of 857 patients, the degree of fibrosis was independent of mild-moderate alcohol consumption [71].…”
Section: Cirrhosis By Blood Tests and Clinicalmentioning
confidence: 99%
“…The risk of HBV, HCV, and HIV is known to be high also in persons with alcohol use disorder. Majority of HCV and HIV cases seen in alcohol use are caused by a history of IDU [9]. Impaired nutrition and self-care, and immunosuppression in persons with alcohol and drug use enable these infectious agents to settle and spread in the body [10].…”
Section: Introductionmentioning
confidence: 99%
“…Impaired nutrition and self-care, and immunosuppression in persons with alcohol and drug use enable these infectious agents to settle and spread in the body [10]. Cocaine, morphine and heroin are known to accelerate intracellular HIV growth [9,11]. Studies investigating coexisting of these infections among the persons with IDU, Hepatitis C virus was also positive in many persons with positive HIV [12].…”
Section: Introductionmentioning
confidence: 99%